2020
DOI: 10.1038/s41598-020-74092-y
|View full text |Cite
|
Sign up to set email alerts
|

Plant secondary metabolites induced electron flux in microbial fuel cell: investigation from laboratory-to-field scale

Abstract: Wastewater treatment coupled with electricity recovery in microbial fuel cell (MFC) prefer mixed anaerobic sludge as inoculum in anodic chamber than pure stain of electroactive bacteria (EAB), due to robustness and syntrophic association. Genetic modification is difficult to adopt for mixed sludge microbes for enhancing power production of MFC. Hence, we demonstrated use of eco-friendly plant secondary metabolites (PSM) with sub-lethal concentrations to enhance the rate of extracellular electron transfer betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Studies have demonstrated that bacteria populations and biofilm compositions in surface and deep-sea water change when exposed to crude oil or chemical dispersants, which is encouraging for the management and cleaning of oil spills. Consequently, bioactive substances show promise in fields including wastewater treatment and hydrocarbon breakdown (Mugge et al, 2021) [72] .…”
Section: Bioremediationmentioning
confidence: 99%
“…Studies have demonstrated that bacteria populations and biofilm compositions in surface and deep-sea water change when exposed to crude oil or chemical dispersants, which is encouraging for the management and cleaning of oil spills. Consequently, bioactive substances show promise in fields including wastewater treatment and hydrocarbon breakdown (Mugge et al, 2021) [72] .…”
Section: Bioremediationmentioning
confidence: 99%
“…They have shown enhanced power density with electron shunting capabilities of a few secondary metabolites such as epigallocatechin-3-gallate, gallic acid, gallocatechin, and anthocyanin. The addition of fungal and algal metabolites in the MFCs improves electricity production (Nath and Ghangrekar 2020). Condensation of β-pinene is processed to form dimers which is an excellent option for a renewable and high energy-density jet fuel and can also be used as diesel (Jung et al 2016).…”
Section: Energy Sectormentioning
confidence: 99%
“…Although soil amendments with waste-biomass-derived carbon materials (e.g., biochar and activated carbon) showed improved microbial interactions, their electrochemical activity can be enhanced further by surface medications with hydrophilic functional groups and altering surface zeta potential. Further research efforts are needed to amend the soil with bioactive additives; for example, the application of leaf extracts with enriched bioactive compounds such as epigallocatechin-3-gallate (EGCG), gallocatechin, gallic acid, and anthocyanin could be a cost-efficient option to enrich the soil for enhanced microbial metabolism [147][148][149][150]. Excellent electrode materials with good stability and catalytic properties are required to be developed; biochar and activated-carbon-modified anode electrodes have shown promising results due to their high activated surface area, but their low electrical conductivity can hamper reaction kinetics at the anode [32].…”
Section: Current Challenges and Future Perspectivesmentioning
confidence: 99%